High-Affinity K(+) Transport in Arabidopsis: AtHAK5 and AKT1 Are Vital for Seedling Establishment and Postgermination Growth under Low-Potassium Conditions(1)([C])([W])([OA]) - Pyo, Young Jae (American Society of Plant Biologists, 2010)
Potassium (K(+)) is a major plant nutrient required for growth and development. It is generally accepted that plant roots absorb K(+) through uptake systems operating at low concentrations (high-affinity transport) and/or high external concentrations (low-affinity transport). To understand the molecular basis of high-affinity K(+) uptake in Arabidopsis (Arabidopsis thaliana), we analyzed loss-of-function mutants in AtHAK5 and AKT1, two transmembrane proteins active in roots. Compared with the wild type under NH(4)(+)-free growth conditions, athak5 mutant plants exhibited growth defects at 10 μm K(+), but at K(+) concentrations of 20 μm and above, athak5 mutants were visibly indistinguishable from the wild type. While germination, scored as radicle emergence, was only slightly decreased in athak5 akt1 double mutants on low-K(+) medium, double mutants failed to grow on medium containing up to 100 μm K(+) and growth was impaired at concentrations up to 450 μm K(+). Moreover, transfer of 3-d-old plants from high to low K(+) concentrations led to growth defects and leaf chlorosis at 10 μm K(+) in athak5 akt1 double mutant plants. Determination of Rb(+)(K(+)) uptake kinetics in wild-type and mutant roots using rubidium ((86)Rb(+)) as a tracer for K(+) revealed that high-affinity Rb(+)(K(+)) uptake into roots is almost completely abolished in double mutants and impaired in single mutants. These results strongly indicate that AtHAK5 and AKT1 are the two major, physiologically relevant molecular entities mediating high-affinity K(+) uptake into roots during seedling establishment and postgermination growth and that residual Rb(+)(K(+)) uptake measured in athak5 akt1 double mutant roots is insufficient to enable plant growth.